THE ROLE OF INTESTINAL MICROBIOTA IN THE PATHOGENESIS OF LATERAL AMIOTROPHIC SCLEROSIS - Abdullaeva M.B.,; U.G.Yodgorova,; Abdunazarov M.M., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In recent years, increasing attention has been paid to the role of intestinal microbiota in the pathogenesis of neurodegenerative diseases, including lateral amyotrophic sclerosis (ALS). The purpose of this work is to analyze modern data on the interaction of microbiota with the central nervous system through the "intestine-brain" axis and to assess its potential participation in the development of ASD. The physiological mechanisms for regulating neural inflammation, barrier function, and metabolic activity of the microbiota, as well as their potential influence on the survival of motor neurons, were considered. A review of preclinical and clinical studies confirming the link between dysbiotic changes in microflora and clinical manifestations of ALS was conducted. Particular attention was paid to microbiota metabolites (butyrate, nicotinamide, propionate) and their neuroprotective effects. The prospects of using probiotics, prebiotics, postbiotics, and fecal transplantation as supplementary therapy for ALS are being discussed. The work's conclusions emphasize the importance of further research on microbiota as a potential therapeutic target in the treatment of neurodegenerative diseases.